2015
DOI: 10.5433/1679-0359.2015v36n1p341
|View full text |Cite
|
Sign up to set email alerts
|

Aspects related to production e storage of Tifton 85 bermudagrass hay with white oat IPR 126 and Guapa oversowing

Abstract: Structural characteristics, curve dehydration, dry matter production, chemical composition, occurrence of fungi, temperature in the storage of hay bales of Tifton 85 oversowing with long-cycle oat (IPR 126) and oats for short-cycle grains production (Guapa), were evaluated. For chemical composition, the experimental design used was randomized blocks, a split-plot overtime and 3 treatments (single Tifton 85, Tifton 85 with IPR 126 oat oversowing and Tifton 85 in association with Guapa white oat and 3 assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The three digestibility variables displayed decreasing linear behavior during storage. This was also reported by AMES et al (2015), who studied Tifton 85 hay and found higher IVDMD at baling than after 30 days of storage. SCHMOELLER et al…”
Section: Santos Et Alsupporting
confidence: 84%
See 1 more Smart Citation
“…The three digestibility variables displayed decreasing linear behavior during storage. This was also reported by AMES et al (2015), who studied Tifton 85 hay and found higher IVDMD at baling than after 30 days of storage. SCHMOELLER et al…”
Section: Santos Et Alsupporting
confidence: 84%
“…The variations in DM content from 60 to 90 days of storage can be explained by the change in climate conditions. Hay is hygroscopic, meaning it can lose and absorb moisture from the environment, influenced by relative humidity (RH%) (AMES et al, 2015).This was confirmed by the increase in environmental RH% in the last two weeks of assessment before the final collection, at 90 days of storage (Figure 1).…”
Section: Resultsmentioning
confidence: 75%